Efforts to improve sprint learning outcomes in physical education learning through a play approach to fourth grade elementary school students - Hidayat, Adi Sukma (Universitas Sebelas Maret, 2021)
This research is motivated by the lack of active student participation in the learning process of physical education, sports and health, so that student learning outcomes are still relatively low. This study aims to improve the learning outcomes of sprinting by applying a play approach in physical education learning in fourth grade students of SD AL QURAN Metro Barat for the 2019/2020 academic year. This type of research is Classroom Action Research. This research was carried out in two cycles, each cycle having 3 meetings. The research subjects were fourth grade students of SD AL QURAN Metro Barat for the 2019/2020 academic year which consisted of 20 students, on the subject of sprinting. Based on the results of data analysis and discussion, it is concluded that the play approach in physical education learning can improve sprint learning outcomes for fourth grade students of SD AL QURAN Metro Barat for the 2019/2020 academic year. This can be seen from the increase in the ability to run fast in the initial conditions (9.675 seconds), cycle I (9.435 seconds) and cycle II (9.24 seconds), so that the increase from the initial condition to cycle II is (0.435 seconds). While the value of mastery learning outcomes in the initial conditions (30%), cycle I (55%) and cycle II (90%), so that the increase from the initial condition to cycle II was (60%).